CT CORONARY ANGIOGRAM WITH FFR CT - A REVOLUTION IN THE DIAGNOSTIC FLOW OF CORONARY ARTERY DISEASE - Raza, Samavia; Efstathiou, Maria (Journal of Ayub Medical College Abbottabad, 2021)
Background: Within the last few years, advances in CT coronary imaging has revolutionised the diagnostic flow of suspected coronary artery disease. CT coronary angiogram has a high diagnostic accuracy and negative predictive value for diagnosis of coronary disease. Its non-invasive nature makes it a lower risk and lower cost procedure compared to conventional invasive coronary angiogram. However, there is restricted value in anatomical evaluation without input regarding the functional significance of each lesion identified with cross-sectional imaging. The gold standard to assess whether a lesion is haemodynamically significant has been the assessment of FFR (fractional flow reserve). fractional flow reserve is the ratio between maximum coronary flow in the presence of stenosis and in the hypothetical absence of stenosis. This is measured invasively by introducing a pressure wire across the lesion involving intracoronary nitro-glycerine as well as intravenous infusion of adenosine. However, the introduction of FFR CT provides information on functional significance of a lesion only using the CT data set of CT CA. Through complex non-linear equations and supercomputing, it produces a three-dimensional model of the coronary artery giving FFR values at multiple point along every major coronary vessel. It is non-invasive, involves no extra dose or contrast and does not require adenosine stress. A lesion that may appear moderate to severe on CT CA with FFR values above 0.80 can be managed by optimal medical management alone. Together FFR Ct and CTCA provide a comprehensive assessment for CAD leading to a reduction in downstream testing and unnecessary revascularisation procedures.